Beyond Macho: The Representation of Generation Z's Soft Masculinity in the Fineshyt Trend on Indonesian TikTok - Firna Sayyidatul Qurroh 'Aini; Nur'annafi Farni Syam Maella; Zulaikha (Ikatan Sarjana Komunikasi Indonesia, 2026)
This study examines the representation of soft masculinity among Indonesian Generation Z males through the “Fineshyt” trend on TikTok. Based on the theories of hybrid masculinity, gender performativity, and multimodal discourse analysis, this study aims to deconstruct how this digital trend produces and normalizes non-aggressive masculine identities. Using a qualitative approach and multimodal discourse analysis methods, 15 TikTok videos with the hashtag #fineshyt from the period July–October 2025 were purposively selected and analysed. The findings show that soft masculinity in this trend is characterized by reflexive protective gestures, emotional control (nonchalance), and the strategic use of point of view (POV) narratives. Collectively, these elements construct an image of masculinity that is calm, situational, and empathetic-protective. However, the analysis also reveals ambivalence: while offering an alternative to hegemonic macho masculinity, this soft masculinity subtly reproduces gender power hierarchies by consistently positioning men as active protectors and women as the protected. This study concludes that the Fineshyt trend represents a rearticulation—not a rejection—of masculine power into a form that is more acceptable in Gen Z's affective-digital culture. This study extends the discourse on affective-digital culture in Indonesia by demonstrating how soft masculinity operates as an affective and algorithmically mediated strategy that rearticulates masculine power through emotionally resonant and multimodal performances.